Seismic behavior assessment of historical Alaeddin Bey Mosque and strengthening suggestions by CFRP fabric and steel plate. (July 2022) - Şentürk, İdris and Ergün, Mustafa and Artar, Musa
Highlights: Determining the seismic vulnerability of historical masonry structures and taking precautions accordingly is of vital importance for the safe transfer of these structures to future generations. Strengthening the masonry with CFRP fabric on only one side reduces the severity of the damage somewhat but does not provide sufficient strengthening efficiency. Strengthening the masonry with CFRP fabric on both sides gives better results than strengthening on one side. The number of CFRP fabric layers has a significant effect on the strengthening effectiveness. The strengthening application made with steel plate shows a better performance than CFRP fabric in terms of reducing the stress intensity in the damaged area. The strengthening application made with the use of steel plate and CFRP fabric together gives very meaningful results. Abstract: In this study, the effects of different strengthening methods that can be applied for earthquake-damaged historical masonry structures on structural performance were investigated. For this purpose, the Historical Alaeddin Bey Mosque in the central district of Muş was modeled in three dimensions according to the macromodeling technique using the finite element method in the SAP2000 program. The earthquake performance of the structure was determined by considering the earthquake-acceleration records of Erzincan, Kocaeli, and Van, respectively. The maximum tensile and compressive stresses in all three directions on the structural elements were taken into account as the earthquake behavior parameters of the structure. According to the earthquake analysis made in the time domain, it was determined that the polygonal pulpit of the minaret was at risk of being damaged under the effect of the Erzincan earthquake, and it has been concluded that this region should be strengthened. The damaged area of the minaret was strengthened by the application of CFRP fabric and steel plate materials (together or separately) in five different ways, from inside and outside and at different distance intervals. The conclusions obtained as a result of the earthquake analyses on the reinforced models were examined, and it was explained in detail with the help of tables and graphics that method would be more effective in strengthening such damages.